2018
DOI: 10.4081/jae.2018.836
|View full text |Cite
|
Sign up to set email alerts
|

Optical sensing for stream flow observations: A review

Abstract: Images are revolutionising the way we sense and characterise the environment by offering higher spatial and temporal coverage in ungauged environments at competitive costs. In this review, we illustrate major image-based approaches that have been lately adopted within the hydrological research community. Although many among such methodologies have been developed some decades ago, recent efforts have been devoted to their transition from laboratories to operational outdoor settings. Sample applications of image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Although the image-based methods for stream velocity have been introduced several years ago, there are still limitations to overcome in order to become a worldwide monitoring system [69]. One of the image-based method limitations is to acquire the correct water level or bathymetry measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Although the image-based methods for stream velocity have been introduced several years ago, there are still limitations to overcome in order to become a worldwide monitoring system [69]. One of the image-based method limitations is to acquire the correct water level or bathymetry measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Optical analysis of the flow may be performed with the use of different methods of data evaluation, including Kanade-Lucas-Tomasi image velocimetry [27], optical tracking velocimetry [28], surface structure image velocimetry [29], space-time image velocimetry [30], and the most explored technique, particle tracking velocimetry (PTV) [31][32][33] and particle image velocimetry (PIV) [34,35]. A comprehensive review of the latter two methods can be found in [36,37]. PTV, a Lagrangian approach, is based on identification and tracking of individual particles across consequent video frames.…”
Section: Introductionmentioning
confidence: 99%
“…PTV, a Lagrangian approach, is based on identification and tracking of individual particles across consequent video frames. It is designed for low density particle distribution and, in most implementations, requires that particles are round-shaped [36]. Some implementations, such as PTV-Stream [38], can deal with tracers of any shape, but they have other limitations, e.g., the necessity to know in advance the direction of the flow average velocity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these methods are expensive and some of them require time-consuming experimental campaigns and the presence of qualified personnel. Intrusive and highly user-assisted technology cannot be adopted to monitor abrupt phenomena, such as flash floods, and large flood events that may be risky for personnel and equipment [8].…”
Section: Introductionmentioning
confidence: 99%